Conceptual issues on Kant’s theory of inner experience (2020)
This paper discusses the use of certain terms associated to I. Kant’s account of inner experience. Inner experience is a subject matter relevant in Kant’s thought, which encompasses metaphysical and anthropological issues worthy of consideration. By examining the Critique of Pure Reason and the Anthropology from a pragmatic point of view, one can see the confused use of the terms: inner sense, empirical, pure, and transcendental apperception, discursive and intuitive self-consciousness, consciousness of oneself divided into reflection and apprehension, intellectual and empirical consciousness of one’s existence. Therefore, I focus on the philosophical meaning of the previous terms and their relation to the problem of inner experience, which depends upon the outer experience. Finally, I deal with the problem of the content of inner sense, suggesting that its content does not correspond to a single, simple thing, but rather to a flux of inner representations.